Reimagining institutional teputation: Crisis-teady internationalization strategies for post-COVID higher education - Steynberg, Lizl; Grundling, Jan (Journal of International Students, 2026)
The COVID-19 pandemic exposed significant vulnerabilities in higher education internationalisation, thereby highlighting the need for more resilient, equitable and crisis-responsive approaches to global engagement. This study examines how higher education institutions (HEIs) can strengthen institutional reputation and internationalisation strategies in the post-pandemic era through the concept of institutional waypower. Adopting a constructivist grounded theory approach, the study employed qualitative documentary analysis for peer-reviewed literature, institutional reports, policy documents and international briefs published between 2020 and 2024. The analysis identified eight interrelated structural adjustment constructs that underpin crisis-resilient internationalisation: crisis-prepared learning management systems (LMSs), technology investment and digital infrastructure, student support and well-being services, internationalisation strategy and intercultural competence, institutional stability and agile governance, ethical stewardship and community engagement, curriculum innovation and responsiveness, and resource development and diversification.